On extraordinary social action: causes and consequences of protest movements - Ebbinghaus, M (2023)
This thesis comprises 7 chapters on the causes and consequences of protest movements. Distinct scholarly contributions on their own, together they advance the field of social movements. My work on the causes of protest movements makes theoretical contributions. First, I revisit the claim that social movements emerged in the 18th century by providing archival evidence that the German peasant movement of the 16th century can be considered a social movement. Second, interviews with 38 BLM activists in Minneapolis reveal that different theoretical arguments can explain protest participation because the motivations for protest change during a protest wave. Third, I use the same interview data to reveal how activists use theoretical arguments to justify riots. Fourth, I use large-scale survey data on protest to identify factors that caused audiences to ally with or oppose the US student movement. My work on the consequences of protest movements is animated by empirical lacunas in existing scholarship. In the fifth contribution, I show that protest can affect institutional outcomes by providing evidence that protest is associated with increases in the admission of Black students to US elite universities. Sixth, I assess local policy outcomes by investigating whether policymakers responded to the demand of the BLM movement that cities “defund the police”. Using original budget data for the 300 largest cities in the US and city-level protest data, I find no evidence that BLM protests caused police defunding, but I find that protests resulted in budget increases in Republican cities. The final chapter on demographic consequences shows with discrete-time event history analysis how protests shape marriage decisions in Ethiopia. Together this thesis uses original quantitative and qualitative data to revisit core questions of the discipline, explore new empirical territory, and show that a multi- methodological approach is suited to capture the complexity of social movements.